Examining Customer Experience and Brand Engagement as Drivers of Customer Loyalty toward Grab Transportation in Makassar City - Adriana; Halik, Johannes Baptista; Londong, Jerliyen Pramita (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This investigation aims to analyse the examining of customer experience and brand engagement on the loyalty of Grab transportation customers in Makassar City using a quantitative approach through questionnaire distribution and multiple linear regression analysis. The regression results show a customer experience coefficient of 0.363 and a brand engagement coefficient of 0.793, indicating a positive effect on customer loyalty. The t-test also proves that customer experience is greatly impacted with a t-value of 7.997 (p = 0.001), and brand engagement is significant with a t-value of 12.866 (p = 0.001). Furthermore, the F test shows the simultaneous effect of both variables with an F count of 118.09 more than the F table of 3.10 (p = 0.001). The coefficient of determination R² of 0.962 indicates that both variables explain 96.2% of the variation in customer loyalty.